Case Report: Preputial reconstruction in a dog using bilateral caudal superficial epigastric axial pattern flap and internal lamina of prepuce - Yala, Wongsuda; Chaikongkiat, Pinprakrom; Khonggrapan, Waralee; Pumpuang, Pornphan; Yippaditr, Wanchart (Frontiers in Veterinary Science, 2025)
A 3.1 kg, 5-year-old male pomeranian presented with a tumor measuring 4.5 × 3 cm on the cranioventral aspect of the prepuce. On gross examination, the tumor did not appear to involve the internal lamina of the prepuce. Surgical intervention was performed using a bilateral caudal superficial epigastric axial pattern flap in combination with the internal preputial lamina following wide tumor resection Follow-up at 10 days and 6 months postoperatively showed the axial pattern flaps had healed uneventfully, with no evidence of paraphimosis and no recurrence of the tumor based on a clinical examination. The dog could urinate without evidence of discomfort and the urine flow was a steady stream without preputial urine pooling, resembling physiological urination. This technique offers a practical and broadly applicable surgical option for managing extensive preputial defects, particularly in small-breed dogs or in cases with limited local tissue availability.